New Old Stock Products’ Distribution - Pabian, Aleksander (European Scientific Journal, ESJ, 2016)
Both new and used products get to sell on the market. The third group consists of products that can be called: new, old stock. One can defined them as new and unused products, which at the same time hit the market later than manufacturer planed and through different channels than were prepared for them. In this article the authors examine how, and under what circumstances a transformation of new products into the old stock happens. Further they consider specific methods for their distribution in the market. An introduction to the discussion is to present the conceptual framework in the field of supply chains’ output side.